2012
DOI: 10.2215/cjn.03660412
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Physical Activity Measured by Accelerometer and Survival in Maintenance Hemodialysis Patients

Abstract: SummaryBackground and objectives The association between mortality and physical activity based on self-report questionnaire in hemodialysis patients has been reported previously. However, because self-report is a subjective assessment, evaluating true physical activity is difficult. This study investigated the prognostic significance of habitual physical activity on 7-year survival in a cohort of clinically stable and adequately dialyzed patients.Design, setting, participants, & measurements A total of 202 Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
100
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 49 publications
2
100
0
2
Order By: Relevance
“…Several other studies indicated that high levels of physical activity were associated with a decreased risk of subsequent cardio-cerebrovascular events in healthy older adults [20,21]. We found in previous studies that a lower level of habitual physical activity is an independent risk factor for all-cause mortality and is closely associated with slow MWS in maintenance HD patients [13,22]. Several previous studies also revealed that HD patients who increased their level of physical activity were able to improve risk factors for cardiocerebrovascular disease, such as hypertension, arterial stiffness, inflammatory reaction, vascular endothelial function, high levels of plasma triglycerides and low levels of high-density lipoprotein cholesterol, dysfunction of the cardiac autonomic nervous system, and reduced maximal oxygen consumption [22][23][24].…”
Section: Discussionsupporting
confidence: 50%
“…Several other studies indicated that high levels of physical activity were associated with a decreased risk of subsequent cardio-cerebrovascular events in healthy older adults [20,21]. We found in previous studies that a lower level of habitual physical activity is an independent risk factor for all-cause mortality and is closely associated with slow MWS in maintenance HD patients [13,22]. Several previous studies also revealed that HD patients who increased their level of physical activity were able to improve risk factors for cardiocerebrovascular disease, such as hypertension, arterial stiffness, inflammatory reaction, vascular endothelial function, high levels of plasma triglycerides and low levels of high-density lipoprotein cholesterol, dysfunction of the cardiac autonomic nervous system, and reduced maximal oxygen consumption [22][23][24].…”
Section: Discussionsupporting
confidence: 50%
“…9,25 Several studies have reported the association of habitual physical inactivity in CKD patients with a high mortality risk. 6,[26][27][28] Despite the finding that the death rate was greater in inactive individuals compared with those with increased physical activity, no studies had yet recognized that physical inactivity in a CKD cohort could be related to exercise intolerance due to pathologically impaired cardiovascular reserve. In this study, we utilized a maximal individualized ramping exercise protocol because submaximal CPET-derived indices of cardiovascular reserve may be further limited by an individual's determination or muscle deconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in patients with CKD and patients on maintenance hemodialysis (MHD) have shown associations of physical activity with improved outcomes (10)(11)(12)(13)(14)(15)(16)(17)(18). However, it is uncertain whether the benefits of types and levels of physical activity apply for different outcomes, such as health-related quality of life (HRQOL), depression, and survival, in patients on MHD with diverse clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%